Problemas historiográficos en la filosofía antigua de India. El sāṅkhya-yoga preclásico y la Kaṭha Upaniṣad - Martino, Gabriel (El Colegio de México, 2017)
We analyze some historiographical problems related to the notions of sāṅkhya and yoga understood as darśanas or philosophical systems. First, we discuss the notion of “classical” in relation to these currents of Indian thought. Then, we examine different conceptions put forward by scholars concerning the gestation and mutual relationship of these two trends. Later, we analyze the Kaṭha Upaniṣad, a text that evinces an early stage in the development of sāṅkhya and yoga. We conclude by confronting our exam of the upanisadic treatise with the historiographical issues first discussed.